The Effect Of Problem Based Learning Model On Learning Motivation And Understanding Of Mathematical Concept Students Of SMP Negeri 2 Tuhemberua - Manurung, Asrar Aspia; Laoli, Desman (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2021)
This research was motivated by the observations of researchers when carrying out learning at SMP Negeri 2 Tuhemberua where the learning carried out did not involve fully active students so that the ability to understand concepts and students' motivation to learn was still lacking. This study aims to determine the effect of the Problem Based Learning learning model on students' learning motivation and understanding of mathematical concepts. This type of research is experimental research using quasi experimental research. The study population was all students of class VIII which consisted of 4 classes with a sample of 2 classes taken by random sampling, namely class VIII-A as the experimental class and class VIII-C as the control class. The data were collected through (1) a student learning motivation questionnaire which was analyzed using a Likert scale, (2) a student's mathematical concept understanding test which was analyzed based on the score of the student's mathematical concept understanding ability test which means "Understanding students' mathematical concepts using the Problem Based learning model. Learning is better than using conventional learning models”.